2006
DOI: 10.3171/jns.2006.105.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Dural involvement in primary extradural meningiomas of the cranial vault

Abstract: Tumor infiltration of the dura should be assumed in PEMs of the cranial vault, and resection of the dura at the site of craniotomy is recommended to prevent tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 94 publications
1
44
0
Order By: Relevance
“…Tumours which are localized in the extrameningeal area, including the intraosseous area, have been known as ectopic tumours [1, 9]. On the basis of their own case studies and the analysis of the professional literature, Lang et al [1] named those tumours as primary extradural meningiomas and suggested the classification into type I (purely extracalvarial), type II (purely calvarial), and type III (calvarial with extracalvarial extension).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tumours which are localized in the extrameningeal area, including the intraosseous area, have been known as ectopic tumours [1, 9]. On the basis of their own case studies and the analysis of the professional literature, Lang et al [1] named those tumours as primary extradural meningiomas and suggested the classification into type I (purely extracalvarial), type II (purely calvarial), and type III (calvarial with extracalvarial extension).…”
Section: Discussionmentioning
confidence: 99%
“…The studies discussing other histological variants of intraosseous meningiomas observed in the CT examination described both the osteolytic and the osteosclerotic lesions [9–15]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations